2013
DOI: 10.1021/nl401277y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Imaging of InN Segregation and Polymorphism in Single Vertically Aligned InGaN/GaN Multi Quantum Well Nanorods by Tip-Enhanced Raman Scattering

Abstract: Vertically aligned GaN nanorod arrays with nonpolar InGaN/GaN multi quantum wells (MQW) were grown by MOVPE on c-plane GaN-on-sapphire templates. The chemical and structural properties of single nanorods are optically investigated with a spatial resolution beyond the diffraction limit using tip-enhanced Raman spectroscopy (TERS). This enables the local mapping of variations in the chemical composition, charge distribution, and strain in the MQW region of the nanorods. Nanoscale fluctuations of the In content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 53 publications
(66 reference statements)
2
42
0
Order By: Relevance
“…4a and c. This modulation induces the breakdown of the translational symmetry of the SO potential creating a larger wave vector along the surface so that the SO mode frequencies are markedly separated from those of the bulk. 20,28,37 In addition to the nanoscale surface modulation, it is important to point out that our vertically and tightly size-controlled nano-LEDs ensure the same orientation of the rod c-axis with respect to the incident light and a constant lling factor of 0.31 AE 0.04 (rod to air area ratio within the laser beam probing diameter). 22,23 By keeping these three features mainly xed through NSL/RIE nanofabrication, we demonstrated the control of the SO mode characteristics such as splitting or symmetry mixing between the axial and planar surface-related phonon modes and their frequencies within small standard deviation values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4a and c. This modulation induces the breakdown of the translational symmetry of the SO potential creating a larger wave vector along the surface so that the SO mode frequencies are markedly separated from those of the bulk. 20,28,37 In addition to the nanoscale surface modulation, it is important to point out that our vertically and tightly size-controlled nano-LEDs ensure the same orientation of the rod c-axis with respect to the incident light and a constant lling factor of 0.31 AE 0.04 (rod to air area ratio within the laser beam probing diameter). 22,23 By keeping these three features mainly xed through NSL/RIE nanofabrication, we demonstrated the control of the SO mode characteristics such as splitting or symmetry mixing between the axial and planar surface-related phonon modes and their frequencies within small standard deviation values.…”
Section: Resultsmentioning
confidence: 99%
“…Another essential point is the impact of intrinsic uctuations in the thickness and In composition on the light emission wavelength from partially or fully strain relaxed nano-LEDs as compared to the bulk strained MQW counterparts. 15,16,20,21 The high surface-to-volume ratio characteristic for the nanorod geometry leads to surface-related phonon modes whose interaction with electrons by way of Fröhlich phonon-electron coupling potentially open the way towards designing of phonon assisted nanorod LED devices. 22,23 Therefore, such basic studies require the fabrication of reproducible nanostructures with small size deviations as well as controlled orientation and density.…”
Section: Introductionmentioning
confidence: 99%
“…A few TERS studies have been reported on III-V nitride semiconductors [79,80]. The relative intensities of the Raman modes have been used to probe orientations of the crystal faces of GaN thin-films at the nanoscale [79].…”
Section: Crystalline and Semiconductor Materialsmentioning
confidence: 99%
“…Nanoscale defects have been identified by means of the forbidden GaN Raman mode at 668 cm −1 , which is otherwise undetectable using conventional Raman spectroscopy due to its weak intensity [79]. Vertically-aligned GaN nanorod arrays with nonpolar InGaN/GaN multi quantum wells (MQW) have been recently investigated using TERS [80]. Fluctuations of a few percent of In content in the InGaN layer were identified with a lateral resolution below 35 nm along with the chemical composition, charge distribution and strain in the MQW [80].…”
Section: Crystalline and Semiconductor Materialsmentioning
confidence: 99%
“…Based on such fundamental PDPs, one can not only examine the strain in bulk nitride materials by non-resonant macro-Raman spectroscopy [19], but also in nanostructures by means of µRaman spectroscopy [20]. Most recently, even tipenhanced Raman spectroscopy [21] was demonstrated for nitrides facilitating strain maps based on PDPs with a lateral resolution well below the diffraction limit.…”
Section: Introductionmentioning
confidence: 99%